Comprehensive evaluation of prophylactic HPV vaccines: a systematic review and meta-analysis of efficacy, safety, and immunogenicity in males and females - Wang, Zhiliang; Zhang, Hui; Zhu, Yuhang; Jiang, Yuanli; Yang, Danhe; Zou, Xiaofeng; Fang, Yi (Frontiers in Immunology, 2026)
BackgroundHuman papillomavirus (HPV) vaccination is a cornerstone of global strategies to prevent HPV-associated malignancies; however, uncertainties persist regarding its long-term efficacy, immunogenicity, and safety across populations, vaccine formulations, and dosing schedules. We conducted a comprehensive systematic review and meta-analysis to evaluate the clinical and immunological effectiveness of prophylactic HPV vaccines.MethodsThis study followed PRISMA guidelines and was registered in PROSPERO (CRD420251050526). Randomized controlled trials (RCTs) were identified through comprehensive searches of six major databases. Risk of bias was assessed using the RoB 2 tool. Meta-analyses were performed using random- or fixed-effects models as appropriate. Subgroup and meta-regression analyses explored the effects of age, sex, vaccine type, dosing regimen, and HIV status. Certainty of evidence was appraised using the GRADE framework.ResultsA total of 145 RCTs were included. HPV vaccination significantly reduced cervical intraepithelial neoplasia grade 1 (RR = 0.15, 95% CI: 0.09–0.24), grade 2 (0.20, 0.13–0.30), and grade 3 (0.48, 0.23–0.98). Persistent HPV16/18 infections were reduced by 84% (0.16, 0.12–0.21), and incident infections by 75% (0.25, 0.19–0.34). Immunogenicity analyses demonstrated robust antibody responses, with fold increases of 3.09 for HPV16, 3.10 for HPV18, 3.48 for HPV6, and 3.37 for HPV11. Tissue-resident CD4+ T cells were significantly reduced (SMD: −1.27, 95% CI: −2.24 to −0.31), while CD8+ T cells showed no significant change. Vaccination was not associated with an increased risk of serious adverse events (0.90, 0.82–0.99) or adverse pregnancy outcomes. Although, injection-site adverse events were modestly increased (1.26, 1.07–1.48).ConclusionProphylactic HPV vaccination provides strong protection against HPV infections and precancerous lesions and induces robust humoral immunity with a favorable safety profile. The nonavalent vaccine, particularly when administered in a three-dose (0/1/6) regimen, offers the most comprehensive protection. These findings support the expansion of gender-neutral vaccination programs to maximize population-level cancer prevention.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251050526.